Eimeria intermedia D. sp., parásita de la lagartija Anolis intermedius Peters - Ruiz, Armando (1959)
Eimeria intermedia n. sp. described from oocysts in the feces of the lizard Anolis intermedius Peters, captured in San José, Costa Rica. The oocysts are ellipsoidal to somewhat ovoid. Twenty five oocysts measured 15, 24 μ. by 10-18 μ, with a mean of 20, 31 by 14,9 μ. Oocyst with a single-layer, smooth wall 0,8 μ thick. Micropyle absent. Sporulated oocysts without oocyst refractile granule or oocyst residuum. Sporocysts 7-7,5 μ, sphercal to subspherical, almost fill oocyst. Sporozoites not well defined, in abundant residual material. HOST: Anolis intermedius Peters. LOCATION: Epithelial cells of gut and intestinal contents. LOCALITY: The host lizard was trapped on March 1959 at San José, Costa Rica.